Penyelesaian Sengketa Tanah Kavling Perumahan Pada Masyarakat Hukum Adat Di Wilayah Kerinci Kecamatan Kumun Debai - Pujha Setiawan. J; Isran Idris (Zaaken: Journal of Civil and Business Law, 2021)
The purpose of this research is to find out and analyze how the legality of the sale and purchase of land according to the decision of the Customary Institution Number: 86 / LA-DPT-IV / Tim-2016, as well as to find out and analyze how the legal process for settling land land disputes for housing lots by the Customary Institutions Dispute Resolution Team which applies to indigenous peoples in the Kerinci area, Kumun Debai District. This research includes juridical empirical research, namely research on the effectiveness of the enforcement of customary law norms. The results of the study show the validity of the sale and purchase of land according to the decision of the Customary Institution of the Dispute Resolution Team Number: 86 / LA-DPT-IV / KD / Tim-2016, invalid, because the decision of the Customary Institution of the Dispute Resolution Team has returned the land condition of the dispute that occurred overlapping due to the wrong transfer of buying and selling to the original position of land belonging to adat means that the sale and purchase of the land in dispute cannot be justified. The legal process for settling disputes in the customary law community of immigrants first reports a complaint request to the Depati IV Kumun Debai Customary Institution to conduct an examination of ownership evidence and then proceed through the dispute resolution team of the Depati IV Kumun Debai customary institution by conducting a customary session of the disputing parties, customary session of witnesses, deliberation, and decisions on dispute resolution.   Abstrak Tujuan penelitian ini adalah untuk mengetahui dan menganalisis bagaimana keabsahan jual beli tanah menurut putusan Lembaga Adat Nomor: 86/LA-DPT-IV/Tim-2016, serta untuk mengetahui dan menganalisis bagaimana proses hukum penyelesaian sengketa tanah kavling perumahan oleh Lembaga Adat Tim Penyelesaian Sengketa yang berlaku bagi masyarakat hukum adat di wilayah Kerinci Kecamatan Kumun Debai. Penelitian ini termasuk penelitian yuridis empiris yaitu penelitian efektivitas keberlakuan norma hukum adat. Hasil penelitian menunjukan keabsahan jual beli tanah menurut putusan Lembaga Adat Tim Penyelesaian Sengketa Nomor: 86/LA-DPT-IV/KD/Tim-2016, tidak sah, karena putusan Lembaga Adat Tim Penyelesaian Sengketa telah mengembalikan kondisi tanah sengketa yang terjadi tumpang tindih akibat peralihan jual beli yang keliru kepada posisi semula asal tanah milik adat artinya menganggap jual beli tanah yang di sengketakan tidak dapat di benarkan. Proses hukum penyelesaian sengketa pada masyarakat hukum adat pendatang terlebih dahulu melakukan laporan permohonan pengaduan kepada Lembaga Adat Depati IV Kumun Debai untuk dilakukan pemeriksaan bukti-bukti kepemilikan dan selanjutnya di proses melalui tim penyelesaian sengketa lembaga adat depati IV kumun debai dengan dilakukan sidang adat pihak bersengketa, sidang adat saksi-saksi, musyawarah, dan putusan penyelesaian sengketa.